2004
DOI: 10.1002/ejoc.200300738
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cycloalkanoindoles by an Unusual DAST‐Triggered Rearrangement Reaction

Abstract: A series of 1,1‐bis(indol‐3‐yl) and 1‐(indol‐2‐yl)‐1‐(indol‐3‐yl)‐ψ‐hydroxyalkanes, prepared from the corresponding indole derivatives and suitable hydroxyaldehydes via routine coupling reactions, were treated with DAST (diethylaminosulfur trifluoride) under mild conditions, to generate a small library of cycloalkanoindoles. Irrespective of the substitution pattern, i.e. whether they are symmetrical or unsymmetrical derivatives, the same mixture of products is produced, in which the tetrahydro‐1H‐carbazole and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…472,473 Giannini and his group found that indole and 5-hydroxypentanal in methanolic hydrochloric acid afford the 2,3′-BIM 260 in 45% yield (Scheme 92). 474 It is worth mentioning that when Dy(OTf) 3 was used as catalyst, 3,3′-BIMs became the predominant product. It appears that protic catalysts favor the formation of 2,3′-BIMs.…”
Section: 3′-bimsmentioning
confidence: 99%
See 1 more Smart Citation
“…472,473 Giannini and his group found that indole and 5-hydroxypentanal in methanolic hydrochloric acid afford the 2,3′-BIM 260 in 45% yield (Scheme 92). 474 It is worth mentioning that when Dy(OTf) 3 was used as catalyst, 3,3′-BIMs became the predominant product. It appears that protic catalysts favor the formation of 2,3′-BIMs.…”
Section: 3′-bimsmentioning
confidence: 99%
“…389 Giannini et al found that both 3,3′-BIMs 339 and 2,3′-BIMs 340 in the presence of diethylaminosulfur trifluoride (DAST) rearrange to the cyclo forms of BIMs 341 and 342 (Scheme 111). 474,528 Using the mentioned synthetic methods, the structureactivity relationship (SAR) of YCH was studied for the following analogues of YCH: 529,530 18).…”
Section: Yuehchukenesmentioning
confidence: 99%
“…The information for 1,1-bis-indolylmethane product 3a was not observed in the presence of Fe 2 (CO) 9 , Fe(OAc) 2 , Fe(acac) 2 , or Fe(acac) 3 (Table , entries 1−4). Comparable yields were obtained when FeCl 2 , FeBr 2 , and FeCl 3 were used as catalysts (Table , entries 5−7) . However, FeI 2 was a less effective catalyst (Table , entry 8).…”
mentioning
confidence: 94%
“…[13] The importance of the developed synthetic approaches to bisindoles of types 3 and 4 is primarily defined by the pharmaceuticaland industrial value of these compounds. Thus, 4-indolyltetrahydrocarbazoles of type 3 are knownt oe xhibit cytotoxic and antiangiogenic activity, [14] whereas indolo[3,2-b]carb- azoles are efficient as aryl hydrocarbon receptor agonists, [15] cyclooxygenase-2 inducersa nd PGE 2 production promoters in cancer cells. [16] Meanwhile, in organice lectronics, they are extensively studied as components of organic field-effect transistors (OFETs), organic light-emitting diodes (OLEDs), dye-sensitized solar cells (DSSCs), and polymer solar cells (PSCs).…”
mentioning
confidence: 99%